Augmented reality marketing: A technology-enabled approach to situated customer experience. Issue 4 (November 2020) - Chylinski, Mathew; Heller, Jonas; Hilken, Tim; Keeling, Debbie Isobel; Mahr, Dominik; de Ruyter, Ko
Highlights: Augmented reality marketing (ARM) is a novel perspective. It embeds and embodies marketing content in customers' environments. Its affordances integrate with digital marketing technologies. The ARM affordances lead to customer experiences of situated cognition. The ARM framework organises future research directions. Abstract: Recent advances in Augmented Reality (AR) technologies have led to a growing interest in their application for marketing strategy and practice – what we term Augmented Reality Marketing (ARM). However, despite emerging publications on the subject, managers and academics struggle to articulate how ARM delivers experiences that are valuable to customers in a way that is different from other marketing approaches. In this article, we review the emerging literature, and define ARM as a customer-facing interface for the application of digital marketing technologies in physical settings. Rooted in a class of 'situated cognition' theories from social psychology, we identify a unique set of digital affordances which ARM offers beyond extant marketing approaches in traditional media. By drawing on the key conceptual building blocks of situated cognition theory, we develop a framework of ARM experiences to synthesize current research and applications, and to suggest directions for future research. Chinese Abstract: 增强现实 (AR) 技术的最新进展使得人们对其在营销策略和实践中的应用越来越感兴趣——我们称之为增强现实营销 (ARM). 然而, 尽管关于这一主题的出版物不断涌现, 管理人员和学者们仍难以阐明 ARM 是如何以一种不同于其他营销方法的方式, 为客户提供有价值的体验的. 在本文中, 我们回顾了新兴的文献, 并将 ARM 定义为在物理环境中应用数字营销技术的面向客户的交互. 植根于社会心理学中的一类"情境认知"理论, 我们确定了 ARM 提供的一套独特的数字启示, 它超出了传统媒体中现有的营销方法. 基于情境认知理论的几个关键理论构架, 我们发展了一个 ARM 的框架, 以综合目前的研究和应用, 并建议未来的研究方向.